(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This paper examines the potential of channeling Nigeria’s pension assets into marginal oil fields to drive economic growth and enhance pension contributors' financial security. Despite holding significant underutilized resources, Nigeria’s marginal oil fields face financial and operational constraints. Meanwhile, pension fund assets have grown exponentially, exceeding ₦20.48 trillion as of September 2024, largely invested (62.03%) in Federal Government Securities. However, federal government bond yields average 18.96%, compared to the oil and gas sector's 28.26% net profit margin, making marginal oil fields an attractive but high-risk investment option for pension funds. The Pension Reform Act of 2014 permits diversified investments, including equities and corporate bonds, yet energy sector investments remain limited. This study develops a conceptual framework assessing the viability of integrating pension assets into marginal fields, emphasizing risk management, return optimization and regulatory alignment. It examines the roles of key stakeholders, including government agencies, pension fund administrators and oil companies, in facilitating this model. Potential risks such as market volatility, regulatory changes and environmental concerns are addressed with strategies like diversification and adherence to ESG (Environmental, Social and Governance) principles. While benefits include higher returns and increased oil production, challenges in regulatory compliance, public perception and sustainability must be managed to ensure success. This analysis contributes to the discourse on alternative investment avenues for Nigeria’s pension assets, thereby offering policy recommendations for a mutually beneficial approach to pension fund involvement in marginal oil field development.